Characterization of aluminum oxide tunnel barriers by combining transport measurements and transmission electron microscopy imaging - Aref, Thomas; Averin, A.; van Dijken, S.; Ferring-Siebert, Anna; Koberidze, M.; Maisi, V. F.; Nguyend, H. Q.; Nieminen, R. M.; Pekola, J. P.; Yao, L. D. (Journal of applied physics, 2014)
We present two approaches for studying the uniformity of a tunnel barrier. The first approach is based on measuring single-electron and two-electron tunneling in a hybrid single-electron transistor. Our measurements indicate that the effective area of a conduction channel is about one order of magnitude larger than predicted by theoretical calculations. With the second method, transmission electron microscopy, we demonstrate that variations in the barrier thickness are a plausible explanation for the larger effective area and an enhancement of higher order tunneling processes.